2018
DOI: 10.1128/microbiolspec.pfs-0023-2018
|View full text |Cite
|
Sign up to set email alerts
|

Nuts and Grains: Microbiology and Preharvest Contamination Risks

Abstract: Low-water-activity foods have been involved in recalls and foodborne disease outbreaks. Increased consumption; better detection methods and reporting systems; improved surveillance, trace-back, and ability to connect sporadic foodborne illnesses; and inadequate implementation of food safety programs are some of the likely reasons for the increase in frequency of recalls and outbreaks linked to dry foods. Nuts and grains can be contaminated with foodborne pathogens at any stage during production, processing, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…The individuals most intensely exposed to such risks are the farmers and field workers in the Ag-SAT field who may come into direct contact with the TWW (WHO, 2006b). Crops that have fruit in contact with soil (e.g., nuts drying on the orchard floor) may not be suitable for Ag-SAT due to the high risk of bacterial pathogen contamination (e.g., salmonella, E. coli) (Brar and Danyluk, 2018). Since Ag-SAT has not, to date, been tested, the health threats stemming from prolonged TWW ponding and the quality of the produced crops are unclear.…”
Section: Health Concernsmentioning
confidence: 99%
“…The individuals most intensely exposed to such risks are the farmers and field workers in the Ag-SAT field who may come into direct contact with the TWW (WHO, 2006b). Crops that have fruit in contact with soil (e.g., nuts drying on the orchard floor) may not be suitable for Ag-SAT due to the high risk of bacterial pathogen contamination (e.g., salmonella, E. coli) (Brar and Danyluk, 2018). Since Ag-SAT has not, to date, been tested, the health threats stemming from prolonged TWW ponding and the quality of the produced crops are unclear.…”
Section: Health Concernsmentioning
confidence: 99%
“…Salmonellosis outbreaks and recalls of nut products due to Salmonella contamination have become increasingly common, raising awareness of nuts as a potential vehicle for foodborne illness. Information about prevalence of human pathogens in nuts is limited (Brar and Danyluk, 2018). Zhang et al (2017) found 4.2% (95% confidence interval 2.40-6.90) Salmonella prevalence in macadamia nuts in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Using historical Salmonella typing data from QLD isolates from various sources collected between 1998 and 2017, we applied a source attribution model to attribute Salmonellapositive macadamia nut samples to animal and environmental source(s). As Salmonella contamination of nuts may be introduced at the plantation site (on the tree or during harvest) or along the postharvest processing path (Brar and Danyluk, 2018), we hypothesized that nonhuman sources in the plantation environment contaminated macadamia nuts.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella enterica is responsible for 78 million illnesses and 59 thousand deaths per year, worldwide (Havelaar et al, 2015). Non-typhoid Salmonella are primarily transmitted via fecal contamination of meat, eggs, dairy products, fruits, nuts, and vegetables (De Buyser et al, 2001;Brar and Danyluk, 2018;De Cesare, 2018;Li et al, 2018;Omer et al, 2018). In the United States, S. enterica causes 1 million illnesses each year, resulting in 19 thousand hospitalizations (Scallan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%